2005
DOI: 10.1093/jac/dki350
|View full text |Cite
|
Sign up to set email alerts
|

Cationic peptide of the male reproductive tract, HE2α, displays antimicrobial activity against Neisseria gonorrhoeae, Staphylococcus aureus and Enterococcus faecalis

Abstract: The peptide HE2alpha, which is derived from the male urogenital tract, exhibits antibacterial activity against both gram-positive and gram-negative pathogens in vitro. The peptide is active against both antibiotic-susceptible and -resistant N. gonorrhoeae isolates. Further investigation of the antimicrobial properties of the peptide is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…Moreover, coagulase-negative staphylococci are well established due to nosocomial bacteremia and indwelling medical device-associated infection, showing increased multidrug resistance (1,14). Thus, the identification of novel agents effective in inhibiting these strains has gained renewed urgency (7). In addition, there is renewed interest in plants with antimicrobial properties as a consequence of current problems associated with the use of antibiotics (4,9).…”
mentioning
confidence: 99%
“…Moreover, coagulase-negative staphylococci are well established due to nosocomial bacteremia and indwelling medical device-associated infection, showing increased multidrug resistance (1,14). Thus, the identification of novel agents effective in inhibiting these strains has gained renewed urgency (7). In addition, there is renewed interest in plants with antimicrobial properties as a consequence of current problems associated with the use of antibiotics (4,9).…”
mentioning
confidence: 99%
“…It has been reported that in men the penile urethra is the entry for various STI-causing pathogens such as Neisseria gonorrhoeae and Chlamydia trachomatis , and urethritis is the most common clinical syndrome [5]. Infection originating from retrograde ascent of pathogens via the ejaculatory ducts, vas deferens, or the blood vessels supplying the epididymis is a common cause of acute epididymitis.…”
Section: Introductionmentioning
confidence: 99%
“…A number of microorganisms infect reproductive tract in humans and animals, with serious consequences for reproductive function [3]. In men, the penile urethra is the portal of entry for pathogens (eg: Neisseria gonorrhoeae and Chlamydia trachomatis) and urethritis is the most common clinical syndrome [4]. Occasionally, these pathogens can also ascend into deeper organs such as the epididymis [4].…”
Section: Introductionmentioning
confidence: 99%
“…In men, the penile urethra is the portal of entry for pathogens (eg: Neisseria gonorrhoeae and Chlamydia trachomatis) and urethritis is the most common clinical syndrome [4]. Occasionally, these pathogens can also ascend into deeper organs such as the epididymis [4]. Retrograde infection of the epididymis may also occur from microorganisms present in the vas deferens, or via the blood vessels supplying epididymis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation